1997
DOI: 10.1115/1.2841191
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Calmed Region Behind a Turbulent Spot

Abstract: Measurements are presented of the calmed region behind triggered wave packets and turbulent spots under a controlled diffusion adverse pressure gradient in a wind tunnel. Similar measurements are also presented from the stator blades of an axial flow compressor, where turbulent spots are induced by the passing of rotor wakes. The purpose is to gain an appreciation of turbulent spot behavior under a strong adverse pressure gradient as a foundation for the more accurate modeling of spots and their environment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…These values are low compared with those typical of aircraft gas turbine engine operation. as reported by Hourmouziadis (1989) and Mayle (1991); they are also generally lower than those in the experimental studies of Halstead et al (1995). The test compressor was nevertheless operating above the critical Reynolds number range where laminar separation stasis to cause a significant increase in blade losses (see Walker.…”
Section: Range Of Investigationmentioning
confidence: 64%
See 1 more Smart Citation
“…These values are low compared with those typical of aircraft gas turbine engine operation. as reported by Hourmouziadis (1989) and Mayle (1991); they are also generally lower than those in the experimental studies of Halstead et al (1995). The test compressor was nevertheless operating above the critical Reynolds number range where laminar separation stasis to cause a significant increase in blade losses (see Walker.…”
Section: Range Of Investigationmentioning
confidence: 64%
“…The recent experiments of Halstead et al (1995), Solomon and Walker (1995a,b) and Solomon (1996) have indicated that transitional flow may cover as much as 70% of compressor airfoil suction surfaces and 50% of turbine airfoil suction surfaces in the presence of periodic wake disturbances. The periodic transitional or turbulent flow strips generated by wake disturbances are followed by regions of relaxing laminar flow with a shear stress higher than steady laminar flow levels.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the interface between the turbulent region and the laminar region, it is necessary to define the turbulent region. In the previous studies (Hedley et al (17) , Gad-el-hak et al (5) , Wygnanski et al (18) , Gostelow et al (11) , and Chong et al (19) ), many methods have been proposed. In this study, the random component of the streamwise velocity signal is used to define a turbulent region.…”
Section: Definition Of the Turbulent Regionmentioning
confidence: 99%
“…Further, the trailing or calmed region of the spot has been investigated by many researchers, and the presence of higher momentum fluid near the wall was revealed (e.g. Antonia et al (10) , Gostelow et al (11) , and Chong et al (12) ). In addition, this characteristic was captured by a theoretical model that was proposed by Brown et al (13) .…”
Section: Introductionmentioning
confidence: 99%
“…A compilation of these findings are provided in Gostelow, Melwani, and Walker (1995). Also, comprehensive investigations have focused on the calmed region (Seifert, 1995, andGostelow et al, 1996).…”
Section: Flat Plate Studies In Wind Ibnneismentioning
confidence: 99%